Comparison of modification of a bacterial uricase with N‐hydroxysuccinimide esters of succinate and carbonate of monomethoxyl poly(ethylene glycol). (28th March 2014) - Zhang, Chun; Yang, Xiaolan; Gao, Ang; Hu, Xiaolei; Pu, Jun; Liu, Hongbo; Feng, Juan; Liao, Juan; Li, Yuanli; Liao, Fei
Abstract Uricase after modification with monomethoxy poly(ethylene glycol) (mPEG) is currently the sole agent to treat refractory gout. For formulating Bacillus fastidious uricase, succinimidyl carbonate of mPEG‐5000 (SC‐mPEG5k) and succinimidyl succinate of mPEG‐5000 (SS‐mPEG5k) were compared. SC‐mPEG5k possessed higher purity, comparable reaction rate constant with glycine but lower hydrolysis rate, and stronger effectiveness to modify amino groups. The uricase possessed two types of amino groups bearing a 25‐fold difference in reactivity with SC‐mPEG5k or SS‐mPEG5k at pH 9.2. Oxonate and xanthine concentration‐dependently protected the bacterial uricase from inactivation during PEGylation. With SC‐mPEG5k at a molar ratio of 200 to uricase subunits and oxonate of 50 µM, the PEGylated uricase (1) retained about 73% of the original activity, (2) displayed about 10% reactivity to rabbit anti‐sera recognizing the native uricase, (3) elicited IgG in rats accounting for about 5% of that by the native uricase, (4) exhibited circulation half‐life time of about 25 H in cock plasma in vivo, and (5) concurrently maintained uric acid at lowered levels for over 20 H. Hence, PEGylation with SC‐mPEG under the protection of a competitive inhibitor was a practical approach to formulation of the bacterial uricase; protection of enzymes by competitive inhibitors during PEGylation may have universal significance.